USAHATANI PURWOCENG (Pimpinella pruatjan Molkenb), POTENSI, PELUANG DAN MASALAH PENGEMBANGANNYA - Yuhono, JT. (Buletin Penelitian Tanaman Rempah dan Obat, 2004)
Potency, opportunity and constraints in development of purwoceng (Pimpinella pruatjan Molkenb)Purwoceng (Pimpinella alpina) farming system, its potency and constraint in development was studied at Dieng area, Wonosobo regency, at September 2003. The location was chosen purposively, considering that the area is the center of origin and the development of purwoceng succeed only at this area. The study was conducted with a survey method, and the samples of farmers were taken by semi- census. The income of purwoceng farming was studied by analysis of income, the potency, prospect and constraint in developing purwoceng were studied byquantitative-descriptive analysis. The results of analysis showed that a net income of Rp. 34.900.000,- for 7 – 8 months yield after harvest was achieved with a 1.000 m square of land. This indicate that developing purwoceng farming system has a good prospect. Until now the demand for purwoceng at Wonosobo regency can not be full filled due to constrain in land that meet the technical requirements for this commodity.